Fundamentals of petrophysics - Yang, Shenglai (Springer geophysics, 2017)
In this book, the fundamental knowledge involved in petroleum & gas development engineering, such as physical and chemical phenomena, physical processes and the relationship between physical factors is covered. It is arranged into 3 Sections. Section 1 including chapter 1-4 is to introduce the properties of fluids (gases, hydrocarbon liquids, and aqueous solutions). Section II including Chapter 5-7 is to introduce the porous rock properties of reservoir rocks. Section III including Chapter 8-10 is to introduce the mechanism of multiphase fluid flow in porous medium. The book is written primarily to serve professionals working in the petroleum engineering field. It can also be used as reference book for postgraduate and undergraduate students as well for the related oil fields in petroleum geology, oil production engineering, reservoir engineering and enhancing oil recovery.